Aromatic Profiling and Bioactive Potentials of Thai Edible Flowers from the Curcuma spp. (Zingiberaceae) - Sarana Rose Sommano; Sureerat Thomya; Pasin Norkum Ai; Julaluk Khemacheewakul; R. Sindhu; Shashanka K. Prasad; Pawenud Thongdang; Apinya Rachkeeree; Methee Wongnak; Prateep Panyadee; Ratchadawan Puangpradab; Ratchuporn Suksathan (Diversity)
This study investigated the aroma profiles, nutritional composition, and bioactive potential of three edible Curcuma species, namely Curcuma candida, C. singularis, and C. petiolata, traditionally consumed in Northern Thailand. An aroma analysis revealed distinct volatile profiles for each species. C. petiolata was qualitatively characterized by high sabinene levels, while β-pinene, limonene, caryophyllene, and humulene were prominent markers for C. candida, and C. singularis exhibited the highest abundance of camphor. A nutritional analysis showed the edible floral tissue of C. petiolata to possess the highest carbohydrate (83.47 g/100 g DW), protein (18.04 g/100 g DW), and energy content (342.83 g/100 g DW). The mineral composition of the edible flowers revealed high levels of macronutrients, including phosphorus (0.36 g/100 g DW), potassium (1.82 g/100 g DW), sodium (0.33 g/100 g DW), and calcium (1.30 g/100 g DW). Palmitic acid (31,098 mg/100 g DW) was the predominant saturated fatty acid, while linoleic acid (45,356 mg/100 g DW) was the most abundant unsaturated fatty acid from these edible flora species. The ethanolic extracts of floral tissues of C. singularis exhibited the highest total phenolic content (0.26 mg GAE/g DW), followed by C. petiolata. Conversely, C. petiolata demonstrated the highest total flavonoid content (0.20 mg QE/g sample), followed by C. singularis (0.11 mg QE/g sample). Antioxidant potential exhibited a significant positive correlation with the quantified total flavonoid content. This research contributes to a deeper understanding of the nutritional and bioactive properties of edible Curcuma flowers, providing valuable information for the development of novel functional foods with unique flavor profiles and potential health benefits.